2012
DOI: 10.1016/j.cortex.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Modality-specific alterations in the perception of emotional stimuli in Bipolar Disorder compared to Healthy Controls and Major Depressive Disorder

Abstract: Objectives Affect identification accuracy paradigms have increasingly been utilized to understand psychiatric illness including Bipolar Disorder (BD) and Major Depressive Disorder (MDD). This investigation focused on perceptual accuracy in affect identification in both visual and auditory domains among patients with BD, relative to Healthy Controls (HC) and patients with MDD. Demographic and clinical variables, in addition to medications were also investigated. Methods The visual Facial Emotion Perception Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 40 publications
5
43
1
Order By: Relevance
“…Several studies have suggested that emotion processing impairments in BD are limited to certain emotions, although there is inconsistency regarding which specific emotions may be affected. Findings have been reported for sadness and fear (Derntl et al, 2009; Vederman et al, 2012), happiness (Lawlor-Savage et al, 2014), and surprise (Summers et al, 2006). Other data suggest a more generalized level of impairment that is not limited to specific emotions per se (Brotman et al, 2008; Van Rheenen and Rossell, 2014).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies have suggested that emotion processing impairments in BD are limited to certain emotions, although there is inconsistency regarding which specific emotions may be affected. Findings have been reported for sadness and fear (Derntl et al, 2009; Vederman et al, 2012), happiness (Lawlor-Savage et al, 2014), and surprise (Summers et al, 2006). Other data suggest a more generalized level of impairment that is not limited to specific emotions per se (Brotman et al, 2008; Van Rheenen and Rossell, 2014).…”
Section: Introductionmentioning
confidence: 90%
“…This study suggested that the two diagnostic groups had a similar level of impairment in emotion identification and differentiation ( d =−.49 and d =−.46 respectively), and that the same results held across a variety of emotion recognition tasks. Data suggest that deficits occur not only during the acute phases of the illness (Lembke and Ketter, 2002; Getz et al, 2003; Gray et al, 2006; Vederman et al, 2012), but also during symptom remission (Bozikas et al, 2006). Although less severe than in schizophrenia (Addington and Addington 1998; Lee et al, 2014), deficits have been shown to be profound in patients with BD who are experiencing acute psychotic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence to indicate that persons with bipolar disorder (BD) are impaired in their ability to process facial expressions (Getz et al, 2003;Lembke and Ketter, 2002;Vederman et al, 2012). However, available research with regards to the prosodic emotion processing profile of BD is narrow and inconsistent at best; there are findings of impaired emotional prosody processing in some studies of euthymic and symptomatic BD groups (Bozikas et al, 2007;Hofer et al, 2010;Murphy and Cutting, 1990) but not others (Edwards et al, 2001;Mitchell et al, 2004;Rossell et al, in press;Vederman et al, 2012), with little explanation for the disparity.…”
Section: Introductionmentioning
confidence: 92%
“…There is evidence of facial affect processing deficits in patients with bipolar disorder at the behavioral, anatomical and functional levels. Several studies have noted that bipolar disorder patients are impaired compared to controls in labeling basic facial emotions (e.g., angry, disgusted, fearful, happy, sad and surprised) (Bozikas et al , 2006, Getz et al , 2003, Kohler et al , 2011, Vederman et al , 2011). Abnormalities in facial affect processing are also evident when using structural and functional MRI (fMRI) methodologies.…”
Section: Introductionmentioning
confidence: 99%